Effects of a functional fatigue protocol on maximal softball hitting. - Bounds, Emilee M. (My University, 2010)
Fatigue can affect athletic performance in many ways, including a decrease in sport specific accuracy, impairments in joint angles, and a decrease in overall muscle performance. In regards to fatigue, little research has been conducted examining the effects of fatigue on baseball and softball performance. The majority of the research stems from examining the effects of fatigue on the overhead throwing motion among collegiate baseball players. Research suggested that as a result of a functional fatigue protocol, baseball pitchers experienced impairments in joint angles in the overhead throwing motion. Among this same population, throwing velocities decreased significantly from the first to last inning pitched, resulting in a great deal of in-game fatigue. Researchers attested that such changes in angles and velocities as a result of fatigue, would negatively affect performance. The purpose of this study was to examine the effects of a functional fatigue protocol on softball hitting form. Additional research, examined the effects of fatigue on performance among skilled tennis athletes. A functional fatigue protocol was implemented, which directly simulated tennis matchplay. Results revealed decreases in tennis hitting accuracy, and just as with the baseball players, fatigue resulted in a decrease in performance. A secondary objective was to identify the relationship between hitting variables, muscular power, and body composition. Participants (n = 6) were NCAA Division II softball players with a mean age of 19.5 Â± 1.4 years who completed a functional fatigue protocol (FFP). The FFP was filmed using a digital video camera, and results were analyzed using Dartfish motion analysis software. To address the secondary objectives, participants completed the Wingate Anaerobic Power test to assess muscular power and a dual-energy x-ray absorptiometry (DXA) scan to discover body composition values. To detect differences in swing angles pre- and post-fatigue, an ANOVA was conducted revealing significant (p < .05) decreases in linear bat-end velocity (LBEV; F = 12.479, p = .017) and batted-ball velocity (BBV; F = 11.856, p = .018) as a result of fatigue. A Pearson's product moment correlation coefficient performed to examine relationships between hitting variables, muscular power, and body composition. Results revealed no significant relationships (p > .05) between muscular power and LBEV or BBV, in addition to no significant relationships between percent fatigue as measured by WAnT or the FFP. Meaningful relationships were discovered between peak power and LBEV and BBV. A strong, negative correlation was present between peak power and BBV (r = -.73, p = .097) and a moderate, negative correlation between peak power and LBEV ( r = -.68, p = .138). Additionally, percent body fat was negatively related to percent fatigue in LBEV(r = -.76, p = .082). Results indicated that fatigue did in fact have a negative effect on softball hitting form, with significant decreases in LBEV and BBV, and that peak power and hitting velocities were inversely related. Although no differences were found in swing angles at ball contact, changes in LBEV and BBV could be detrimental to swing timing and performance. Results of this study will be utilized to further understand the effects of fatigue on softball hitting form and the role of muscular power and body composition on hitting performance.
Keywords: Women softball players; Batting (Softball); Fatigue